Elementos teóricos da filosofia de Peirce associados aos conceitos de crença e hábito - Vasconcelos Junior, D’Arthagnan Carlos (2023)
The ethical principles followed by Jesus thus become decisive in a renewed Christian ethics proposal, oriented by its sources and sensitive to the signs of the times, as Vatican Council II requests to Moral Theology, aiming to think of new economic logic and an integral education. In this way, the research seeks to problematize which path(s) are possible to the formation of Christian conscience on contemporary in three stages: in the first one, seeks to understand contours of the so-called postmodern reality; in the following one, verifies how José María Castillo’ Christology can illuminate the formation of conscience’s process, offering important ethical principles; in the last one, how these principles can be assumed and shape the contemporary individuals’ conscience and life, as through overcoming pessimism, freedom assumption and the joining of forces to change reality endorsing, for example, the current pontificate’s efforts in seek of a new face to economy and an integral e communitarian education of individual. KEY-WORDS: Post-modern context; Formation; Conscience; Christological ethics.